Impact of Heavy Metal Pollution on the Environment - Lubal , Maruti J. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Pollution of the environment by the toxic heavy metals is a global issue of concern and affects the natural quality of the air, water, and soil. Anthropogenic activities are largely responsible for the widespread pollution of heavy metals in the environment, which is having a harmful impact on human health. Rapid urbanization, industrialization, population explosion, and use of advanced technology in developing countries have resulted in huge rise in waste production. Waste generation and disposal along with landfills is a serious global environmental threat resulting in heavy metal contamination of the soils, water, and plants. Heavy metals reaching in the atmosphere result to the deterioration of the quality, and contamination of the soil and groundwater along with damage to the living organisms. The present review describes the analysis of heavy metal pollution of the environment with respect to air, animals, aquatic ecosystem, plants, and soil. Special emphasis is provided on sources of heavy metals in the environment, harmful impacts of heavy metals on the environment and strategies to control heavy metal pollution of the environment. Present study is based on critical review and analysis of scientific information published by academic and professional researchers who studied the impact of heavy metal pollution on the environment. Research articles on impact of heavy metal pollution on the environment published in high impact factor journals were referred for collection of databases. This study notices that there is an urgent need for continuous monitoring of various environmental elements for heavy metals in different open dumpsites. It also recommends that nanomaterials, such as metal oxide nanoparticles, graphene and its derivatives, magnetic nanoparticles, and carbon nanotubes should be used to remove the toxic heavy metals from the air, water and soil.